Dietary, socioeconomic, and maize handling practices associated with aflatoxin and fumonisin exposure among women tortilla makers in 5 departments in Guatemala. - Ariel V Garsow; Olga R Torres; Jorge A Matute; Danielle M Voss; Gonzalo Miyagusuku-Cruzado; M Monica Giusti; Barbara B Kowalcyk (Public Library of Science (PLoS), 2024)
Previous research has demonstrated human exposure to mycotoxins among Guatemalans, with high levels of mycotoxins being found in blood and urine samples as well as in maize for human consumption. Mishandling of crops such as maize during pre- and post-harvest has been associated with mycotoxin contamination. The overarching goal of this study was to identify risk factors for aflatoxin and fumonisin exposure in Guatemala. A cross-sectional survey of 141 women tortilla makers was conducted in the departments of Guatemala, Sololá, Suchitepéquez, Izabal, and Zacapa in February 2022. Maize and tortilla samples were collected and analyzed for aflatoxin B1 (AFB1) and fumonisin B1, B2, and B3 contamination (FB1, FB2, FB3). Urine samples were collected and analyzed for urinary FB1 (uFB1) contamination. A questionnaire was administered to collect data on sociodemographic characteristics, dietary intake of maize-based foods the week prior to the study, and maize handling practices. Descriptive statistics were used to describe common maize handling practices. A univariable analysis was conducted to identify predictors of low/high AFB1, total fumonisins, and uFB1. Multivariable logistic regression was used to calculate adjusted odds ratios (ORs) and 95% confidence intervals (CIs). During tortilla processing, a reduction in the AFB1 and total fumonisin levels was observed. The presence of AFB1 in maize was associated with department and mean total fumonisin level in maize (OR: 1.705, 95% CI: 1.113-2.613). The department where the tortilleria was located was significantly associated with the presence of fumonisins in tortillas. Increased consumption of Tortrix was significantly associated with the presence of FB1 in urine (OR: 1.652, 95% CI: 1.072-2.546). Results of this study can be used in the development and implementation of supply chain management practices that mitigate mycotoxin production, reduce food waste and economic loss, and promote food security.